International Diversification: Effects on Innovation and Firm Performance in Product-Diversified Firms - Hitt, Michael A.; Hoskisson, Robert E.; Kim, Hicheon (Academy of Management Journal, 1997)
Theory suggests and results show that firm performance is initially positive but eventually levels off and becomes negative as international diversification increases. Product diversification moderates the relationship between international diversification and performance. International diversification is negatively related to performance in nondiversified firms, positively related in highly product-diversified firms, and curvilinearly related in moderately product-diversified firms. International diversification is also positively related to R&D intensity, but the interaction effects with product diversification are negative. The results of this study provide evidence of the importance of international diversification for competitive advantage but also suggest the complexities of implementing it to achieve these advantages in product-diversified firms.